Assessment of filtration water spreading on the surface of waterbodies - Rashkevich, Nina (Lviv Politechnic Publishing House, 2018)
The paper is devoted to the development of the nonlinear mathematical model which describes the spreading of the liquid fraction of solid waste decomposition products on the surface of waterbodies. The solution to the problem of a lighter liquid fraction spreading is divided into three stages – the gravitational and inertial stage, the stage of surface tension and viscosity, and the gravitational and viscous stage. The author assesses the impact of dynamic processes оn the nature of waterbodies pollution.
Keywords: filtration waters; liquid floaty fraction; waterbodies; spreading stages; dynamic processes